Curcumin mediated down‐regulation of αVβ3 integrin and up‐regulation of pyruvate dehydrogenase kinase 4 (PDK4) in Erlotinib resistant SW480 colon cancer cells. (23rd November 2017) - Javadi, Samira; Rostamizadeh, Kobra; Hejazi, Jalal; Parsa, Maliheh; Fathi, Mojtaba
Abstract : Erlotinib is a potent, selective, and orally active inhibitor of the epidermal growth factor receptor, but the development of erlotinib resistance during chemotherapy can lead to treatment failure. To shed light on the erlotinib‐resistant pathway, this study investigated the effect of combination therapy using curcumin‐ and erlotinib‐loaded nanoparticles on the expression of αv β3 integrin and pyruvate dehydrogenase kinase 4 (PDK4) in an erlotinib‐resistant SW480 colon cancer cell line. An erlotinib‐resistant SW480 colon cancer cell line was produced by long‐term exposure to erlotinib. Curcumin‐loaded Methoxy poly ethylene glycol Poly caprolactone (cur/mPEG‐PCL) and erlotinib‐loaded mPEG‐PCL (erl/mPEG‐PCL) micelles were provided using a single step nanoprecipitation method and used as combination therapy of resistant SW480 cancer cells. After that, gene expression levels of PDK4, αv, and β3 mRNA were determined by the semiquantitative reverse transcription‐polymerase chain reaction. Protein levels of whole αv β3 integrin were evaluated using the enzyme‐linked immunosorbent assay method. In SW480 cell line, the IC50 of nonresistant and resistant cells was 87.6 ± 1.2 nM and 19.1 ± 0.14 μM, for erlotinib and it was about 21.8 and 30 μM for curcumin, respectively. Although PDK4 expression was not significantly different in resistant and nonresistant cells, its expression was up regulated (1.4 fold) in resistant cells by a combination therapy of cur/mPEG‐PCL at a dose of 3 μM and erl/mPEG‐PCL at a dose of 5 μM. β3 mRNA and the protein level of whole αv β3 integrin was significantly higher in resistant SW480 cells as compared with those in nonresistant cells. In terms of treatment, a combination of 6‐μM cur/mPEG‐PCL and 5‐μM erl/mPEG‐PCL down regulated β3 gene expression 6.6‐fold in resistant cells as compared with nonresistant cells. At the protein level, a combination of 3‐μM‐cur/mPEG‐PCL and 10‐μM erl/mPEG‐PCL reduced αv β3 protein in resistant cells. The results indicated that combination therapy using cur/mPEG‐PCL and erl/mPEG‐PCL could decrease αv β3 integrin expression and increase PDK4 gene expression in resistant colon cancer cells, which may have effects on drug resistance signaling pathways.